2008
DOI: 10.3176/oil.2008.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Kinetics and Mechanisms of Thermal Decomposition of Moroccan Tarfaya Oil Shale and Its Kerogen

Abstract: In this research, thermal characteristics and kinetic parameters of Tarfaya oil shale and its kerogen samples were determined by thermogravimetry (TG/DTG) under non-isothermal heating conditions. The pyrolysis experiments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 30 publications
6
73
3
1
Order By: Relevance
“…It is found that the shapes of the TG/DTG curves are shifted laterally with increasing heating rate. The onset temperature, peak temperature, and the rate of mass loss also shifted laterally due to the variation in the heating rates and short exposure time to a particular temperature at higher heating rates, which affects the kinetics of decomposition of the samples [27,42]. It is also observed that the TG/DTA exothermic peak shifted laterally towards the higher temperatures with the increase in heating rate where the maximum mass loss occurs (Fig.…”
Section: Reactivity Test Of the Carbonized Acfsmentioning
confidence: 66%
See 1 more Smart Citation
“…It is found that the shapes of the TG/DTG curves are shifted laterally with increasing heating rate. The onset temperature, peak temperature, and the rate of mass loss also shifted laterally due to the variation in the heating rates and short exposure time to a particular temperature at higher heating rates, which affects the kinetics of decomposition of the samples [27,42]. It is also observed that the TG/DTA exothermic peak shifted laterally towards the higher temperatures with the increase in heating rate where the maximum mass loss occurs (Fig.…”
Section: Reactivity Test Of the Carbonized Acfsmentioning
confidence: 66%
“…Several researchers have applied the model-free method on the thermogravimetric (TG) data to evaluate the kinetic parameter of coal, biomass, and coal-biomass blends [4,7,8,11,12]. Aboulkas et al [27] and Budrugeac [3] have also applied the model-free method on the TG data to evaluate to evaluate the kinetic parameter of Tarfaya oil shale, its included kerogen samples, and a composite epoxy resin material, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Oil shale is a fine-grained sedimentary rock containing large quantities of organic matter capable of yielding oil upon retorting, with an oil content of 3.5-30%. When heated above 500 • C in an oxygen-poor environment, it can yield shale oil, which has a significant role in mitigating the pressure of oil crisis as an alternative to oil energy in some industrial production [3]. Oil shale is commonly associated with coal, and both coal and oil shale can be slowly oxidized in goafs resulting in a temperature increase and flammable gases release.…”
Section: Introductionmentioning
confidence: 99%
“…Oil shale pyrolysis using thermogravimetric 20 analysis has been previously investigated 9,49,50 . It was found that, depending on the oil shale 21 type, its decomposition exhibits either single or a two-stage evolution of hydrocarbon material, in 22 the temperature range of 250 -620ºC.…”
mentioning
confidence: 99%
“…This is a carbonaceous material from which oil and combustible gas can be 15 extracted by destructive distillation 6 . Several studies have been carried out concerning the 16 characterization of different oil shale types and their potential for liquid hydrocarbon generation 17 [7][8][9] . The most important techniques used for characterization of potential source rocks are Eval pyrolysis 10 , vitrinite reflectance measurements, X-Ray diffraction, FTIR and thermal 19 analysis (DTA-TGA).…”
mentioning
confidence: 99%